(3GdYeOI aj GdNWs - (3YHO Gddg Hf Ydj Hf YHO Gddg GdgjJj, LeGd GdOjf,J (B891 (3g` s
(3ChdgG (B:s
(3hHYO GdHSedI GdJi HYV GNhGfi hCUMGHi hCMHGHi ef WGdHi Yde GdcJGHg s
(3BNQgG (B:s
(3hgPg GdCTcGd GdCQHYI JONd ai LejY GdGbdGe cdgG s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B106s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B197 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3VHGYg (B15) s
Keywords: (3GdNW hCdGJgs